1998
DOI: 10.1016/s0008-6363(97)00327-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mitogen-activated protein kinases and activator protein-1 in myocardial infarction in rats

Abstract: Myocardial ischemia increased MAPK activities, which were followed by enhancement of AP-1 and NF-kB DNA binding activity in areas of myocardial infarction in rats. These signal transduction mechanisms may contribute to the myocardial ischemia and injury associated with myocardial infarction by causing an increased expression of TGF-beta-1 mRNA, collagen I and III in the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 41 publications
7
75
3
Order By: Relevance
“…It is worth noting that ischemia by itself activated the JNK pathway. These results are in agreement with a small number of previous studies (24,28,31) while contrasting with many other reports showing specific activation of JNK on reoxygenation-reperfusion (10,14,18,20,22,26,30). JNK activation during reperfusion was confirmed by a modest yet significant increase in the amounts of phosphorylated c-Jun protein in nuclear extracts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is worth noting that ischemia by itself activated the JNK pathway. These results are in agreement with a small number of previous studies (24,28,31) while contrasting with many other reports showing specific activation of JNK on reoxygenation-reperfusion (10,14,18,20,22,26,30). JNK activation during reperfusion was confirmed by a modest yet significant increase in the amounts of phosphorylated c-Jun protein in nuclear extracts.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies in isolated cardiomyocytes (20,26), isolated-perfused rat hearts (10,18,22,30), and rat hearts in vivo (14) suggested that activation of JNK occurs specifically on reoxygenationreperfusion. However, other studies in isolated rat hearts (31) as well as in rat and rabbit hearts in vivo (24,28) suggested that ischemia by itself can activate the JNK pathway. Likewise, the role of JNK in myocardial I/R remains controversial, since equally robust studies have reported dichotomous results suggesting both cardioprotective (1,12,13,27) and detrimental (2,15,16,19,21,25) effects.…”
mentioning
confidence: 98%
“…A retrograde perfusion of the heart was carried out for 10 min by the Langendorff mode and then switched to perfusion according to the working-heart technique (16). The perfusion fluid was a Krebs-Henseleit buffer (pH 7.4) of the following composition (in mmol/l): NaCl, 118; NaHCO 3 To initiate total global ischemia, the perfusion pump was turned off for 30 min after an initial 30-min equilibration period. After ischemia, hearts were reperfused by restoring flow to the control level for an additional 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that ischemia with subsequent reperfusion of the myocardium is associated with inflammation, necrosis, and apoptosis, and that the activation of several stress-related proteins plays a major role in their genesis. Members of the mitogen-activated protein (MAP) kinase family, in particular Jun NH 2 -terminal kinase (JNK), have been demonstrated to be activated by reperfusion, both in vitro (1,2) and in vivo (3). Upon activation, JNK induces transcriptional activity by phosphorylation of c-Jun (4), thereby enhancing activating protein-1 (AP-1) DNA-binding activity (3) and, in cardiac tissue, leading to cell apoptosis (5).…”
mentioning
confidence: 99%
“…Myocardial ischemia and hypoxia activate the MAPKs and the transcription factor, AP-1 (85). AP-1 is an important factor in the activation of ET-1 and the Ras-MAPK signaling pathway is critical to the activation of AP-1 (Figure 1).…”
Section: Mitogen Activated Protein Kinase (Mapk) Cascadementioning
confidence: 99%